Hubungan antara Gaya Hidup Sehat dengan Tingkat Stres Siswa Kelas XII SMA Negeri di Denpasar Menjelang Ujian Nasional Berdasarkan Strategi Coping Stres (Jurnal Psikologi Udayana, 2013)
National examination is a standard passing score that has been set by the government to meet national educational competencies. Students who implant the positive values to healthy lifestyle in their daily lives, it will be able to manage themselves with appropriate coping strategies to get out of stressful situations that push. Quantitative research with regression analysis method aimed to see the relationship between healthy lifestyle with stress level of twelfth grade students of high school in Denpasar towards final examination based on stress coping strategy, like problem focused coping and emotion focused coping.Sampling technique uses cluster random sampling with 317 subjects of twelfth grade students in Denpasar. Measuring instrument in this study is the healthy lifestyle scale (reliability 0.846), stress level scale (reliability 0.913), and stress coping strategies scale (reliability 0.868). Z-score test and regression analysis were used to divide into groups with 143 subjects coping strategies in problem focused coping (p